2014
DOI: 10.1177/1049909114523827
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of a Novel Interdisciplinary Model for Advanced Illness Management

Abstract: Study findings suggest @HOMe Support is associated with reductions in the use and cost for most health services over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…In psychological care context (Tsai et al, ) of chronic conditions, the hospital‐based home healthcare compared to traditional outpatient follow‐up approach showed that the costs of the hospital‐based home care model were lower than those of conventional outpatient follow‐up and that over a 1‐year period, the hospital‐based home‐care model was associated with improvements in mental conditions, social functional outcomes, and service satisfaction . In accordance with the study of Hopp et al (), hospital‐based inter‐professional chronic care model reduced costs significantly for patients older than 65 years , but not for patients younger than 65 years.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In psychological care context (Tsai et al, ) of chronic conditions, the hospital‐based home healthcare compared to traditional outpatient follow‐up approach showed that the costs of the hospital‐based home care model were lower than those of conventional outpatient follow‐up and that over a 1‐year period, the hospital‐based home‐care model was associated with improvements in mental conditions, social functional outcomes, and service satisfaction . In accordance with the study of Hopp et al (), hospital‐based inter‐professional chronic care model reduced costs significantly for patients older than 65 years , but not for patients younger than 65 years.…”
Section: Resultssupporting
confidence: 85%
“…Still again, no consensus was seen regarding whether these service forms affected length of hospital stay or costs when compared to inpatient care. However, an interprofessional intervention for chronic patients resulted in a significant declination in costs for patients 65 years and older (Hopp et al, ). In advanced care at home, patients and their family caregivers experienced advanced care at home as very secure (Johansson & Westman, ; Lee et al, ; Lundin, ; Pusa et al, ), but the research results on care costs and service use were ambiguous due to different cost calculations (Dowell et al, ; Popejoy et al, ; Ryu, ; Tsai, Chen, & Yin, ) and the fact that informal care by family caregivers is not included in such calculations (Andersson, ).…”
Section: Resultsmentioning
confidence: 99%
“…These common elements included the use of comprehensive assessments (Meyer, 2011), focusing on a target population (Naylor et al, 2007), and developing care plans with patient-centered goals (Reuben, 2011). As with LifeCourse, the majority of the programs utilized home visits to some degree and had an interdisciplinary team to provide care (Hoefer, Johnson, & Bender, 2013; Hopp et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…One such program is the Hospice of Michigan's At Home Support (AHS) program, 7 which has been demonstrated to reduce health-care costs while providing high-quality care for patients. 8 Although AHS demonstrated mean cost savings, the healthcare utilization of participants was variable. Little is known about what elements of outpatient palliative programs are most valuable and for which participants.…”
Section: Introductionmentioning
confidence: 99%
“…One such program is the Hospice of Michigan’s At Home Support (AHS) program, 7 which has been demonstrated to reduce health-care costs while providing high-quality care for patients. 8…”
Section: Introductionmentioning
confidence: 99%